Help mehbbhhhnkjdddddddddddddddddfffffggggg

4x - 3 = 5x - 17

Here, you have an equation composed of two equations ( 4x - 3 and 5x - 17 ) that are set equal to each other. Your goal is to solve for the unknown variable, x, by isolating the x variable to one side of the equation. To do so, move all terms containing x to one side of the equation and move all other terms to the other side, then combine like terms:

4x - 3 = 5x - 17

- 4x - 4x

______________________

4x - 4x - 3 = 5x - 4x - 17

0x - 3 = 1x - 17 ==> -3 = x - 17

+ 17 + 17

_____________________

-3 + 17 = x - 17 + 17

14 = x + 0 ==>
**x = 14**